: - Deva Yulinda; Suci Ramadhani Putri (Fakultas Syariah IAIN Madura, 2023)
This article aims to find out how the stereotyping of housewives as unemployed women in the Population and Civil Registration Service (Dukcapil) of North Lombok Regency (KLU) and how to gender analysis of this. This research is qualitative research that aims to describe various stereotypical problems towards housewives using a gender analysis approach. This research was conducted at Dukcapil KLU. This article argues that stereotyping of housewives is a form of embodiment of the theory of